2009
DOI: 10.1021/ja903479p
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structures of Lithium Enolates of Cyclopentanone, Cyclohexanone, Acetophenones, and Benzyl Ketones. Triple Ions and Higher Lithiate Complexes

Abstract: Multinuclear NMR spectroscopic studies at low temperature (-110 to -150 degrees C) revealed that lithium p-fluorophenolate and the lithium enolates of cyclohexanone, cyclopentanone and 4-fluoroacetophenone have tetrameric structures in THF/Et(2)O and THF/Et(2)O-HMPA by study of the effects of the addition of HMPA. The Z and E isomers of the lithium enolate of 1,3-bis-(4-fluorophenyl)-2-propanone (5F-Li) show divergent behavior. The Z isomer is completely dimeric in pure diethyl ether, and mostly dimeric in 3:2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 76 publications
0
22
0
Order By: Relevance
“…While experimental observations indicate that enolates derived from these ketones are oxidized, hydrogen atom abstraction from THF coordinated to the lithium centers of the aggregates becomes a competitive pathway. 16, 17 …”
mentioning
confidence: 99%
“…While experimental observations indicate that enolates derived from these ketones are oxidized, hydrogen atom abstraction from THF coordinated to the lithium centers of the aggregates becomes a competitive pathway. 16, 17 …”
mentioning
confidence: 99%
“…Besides lithiated thioethers and dithianes,, the focus of our collaboration was on Li‐enolates,,, workhorses of organic synthesis, see the ketone ( 1 ), ester ( 2 ), and amide ( 3 ) Li‐enolates and a Li‐dienolate ( 1c ) in Figure . They are all dimeric or tetrameric aggregates in the solid state (and, as shown by others, also in solution) . What have we learned from the Li‐enolate structures?…”
Section: Meeting Of a Synthetic Methodologist With An X‐ray Crystallmentioning
confidence: 82%
“…Even though a lithium enolate can be expressed as ROLi, its composition in a real solution is far more complex. In polar solvents like THF (and in the absence of chelating agents) lithium enolates are cubic tetramers,23 although in some cases dimers can be formed and, in the presence of additives, monomers can also be present 24. A computational study carried out with the lithium enolate derived from acetaldehyde demonstrated that monomeric species is important in the equilibrium due to its high solvation energies,25 although more recent calculations showed that tetramer is the major species in THF, monomeric species being preferred in the presence of chelating agents 26.…”
Section: Resultsmentioning
confidence: 99%